The civilizational cycle in the state according to Iben Khaldoun Cycle de civilisation dans l'État selon Iben Khaldoun - saoudi, meftah (Journal of Social Sciences and Humanities, 2023)
This study aims to clarify the role of nervousness in the state, in order to understand the five phases that the state goes through, and the role of nervousness in the transition from the nature of nomadism to the character of civilization, because the state in the midst of that passes through three generations, like the human case, it is It is born, grows and disappears, interrupting a circular civilized cycle, as this cyclical succession makes the state as a political and social entity that moves from one stage to another, and is based on foundations that follow it, especially the close relationship between sectarianism and the state, and the role that nervousness plays in its establishment. It was considered an important part in the emergence of the state. Because phases and generations make the state cut a circular motion along its civilizational path. Because the whole of civilization is nomadic, civilization and king, it has a tangible life like the life of a human being, as the ages do not exceed three generations, and the building of the king is two foundations: the first is thorn and nervousness, and it is manifested in the soldiers. The second is in money or the economy, which is the strength of the soldiers and what the king needs. The concept of the state in Khaldounian thought is not an abstract concept that can be isolated from its historical environment, and it is not a historical concept deduced from certain systems. The establishment and stability of the state transfers the ruling fanaticism to a civilized stage, in which new influences begin, transferring the conflict from outside the aforementioned fanaticism to its interior. From the generation of revolution and nomadism, to the generation of luxury. Iben Khaldoun presented his theory of the development of states in terms of the general conditions of the state, the shape of the state, its institutions, its phases, the different conditions and the creation of its people in different phases.